Pengaruh jumlah nasabah, tingkat suku bunga dan inflasi terhadap penyaluran kredit pada pt pegadaian di cabang samarinda seberang kota samarinda - Ade Septevany Dewi (Faculty of Economics and Business Mulawarman University, 2016)
Testing the hypothesis in this study using multiple regression analysis models due diligence. Multiple regression analysis was used to determine the effect the effect of several independent variables on the dependent simultaneously or partially during any particular period. The results of the analysis obtained by linear regression equation as follows:Y = -119.190 + 0,024X1 + 82,319X2 - 0,157X3 Results of simple linear regression equation that shows the direction of the effect of each - each independent variable on the dependent variable, which is indicated by the regression coefficient variable. unknown value of R square (coefficient) of 0.917 or 91.7%. This means that 91.7% Loans (Y) on PT Pawn (Persero) Branch in Samarinda across the city of Samarinda is affected by the number of customers (X1), Interest rate (X2) and inflation (X3), while the remaining 8.3 % is the contribution of other factors not included in this study. The results of the analysis and discussion of the conclusions made are number of customers affect the loan portfolio in PT Pawn (Persero) Branch in Samarinda Seberang Kota Samarinda hypothetically accepted. The interest rate does not affect the loan portfolio in PT Pawn (Persero) Branch in Samarinda Seberang Kota Samarinda is the hypothesis is rejected. Inflation effect on Mortgage Lending in PT (Persero) Branch in Samarinda Seberang Kota Samarinda is the hypothesis is rejected.Keyword: The interest rate, inflation, and Lending